Análise socioambiental da microbacia hidrografia do Zé Açu, Parintins - Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
The Hydrographic Microbasin (Mbh) of Zé Açu, as in many places in the Amazon, presents itself as a territory of conflicts of interest. The most evident economic activity in this microbasin is the extensive cattle raising with cattle and buffaloes, with the peak of production reaching 10,000 heads in the region during the 1990s, stabilizing between 2,000 and 2,500 head between the years of 2013 to 2016 according to ADAF estimates. Located in the East sector, the urban perimeter of the Municipality of Parintins in linear distance approximately 11 km from that city. According to the studies developed by Pachêco (2013), it covers an area of 126,923 km2, occupied by nine communities whose denominations are expressed as follows: Nossa Senhora de Nazaré, Bom Socorro, Paraíso and Nossa Senhora das Graças located in the bands near the banks of the Zé Açu. Brazil Roça, Boa Esperança, Santa Fe, Nova Esperança and Vista Alegre are located within the INCRA Vila Amazonia Settlement Project. However, in order to carry out this socio-environmental analysis, with regard to population aspects and community nuclei, this research was limited to studying the communities located on the banks of the Zé Açu Hydrographic Basin (Mbh), where approximately 350 families live, , Our Lady of Nazareth, Good Socorro of Zé Açu, Our Lady of Grace and Paradise. Among the socioenvironmental problems found in the Mbh of Zé Açu, soil degradation is highlighted through erosion. In this sense, the most critical problem is the sedimentation that promoted the degradation in the existing headwaters up to the middle of the Zé Açu, damaging mainly the families that still use water from the river for consumption, as is the case of 64 (sixty-four ) residences away from the community nuclei identified in this study. These implications resulted, among other consequences, in a strong pressure for land abandonment, resulting in the reduction of 59% of the initial population of the community most affected by environmental degradation. At the end of the research, we can point to the suppression of native vegetation as the driving force of a chain of processes that has resulted in the increasingly degraded environment analyzed by this study.
Keywords: Bacias Hidrográficas; Análise Socioambiental; Análise Socioambiental; Erosão; CNPQ: CIENCIAS HUMANAS: GEOGRAFIA